The using an ecological marketing on enterprises of Republic Kazakhstan - Kozhamkulova, Zh. T.; Sarsenova, A. S. (Journal of Economic Research & Business Administration, 2016)
To date, with an increase of uncultivated industrial waste, air pollution, lakes and rivers, deteriorating health, as well as the emergence of various diseases are closely linked with the growing ecological problems, the solution of which is of great importance. Global organizations, enterprises are considering environmental issues at a high level and to avoid these problems ecological marketing was used, and in Kazakhstan this experience is not developed to a sufficient level. The President of Kazakhstan Nursultan Nazarbayev in his message to the people "Strategy 2050" says that we must create a national domestic brand, which will be competitive and meet ecological standards. Therefore it is very important to determine consumer demand for environmentally-friendly and safe products, implement ecological marketing strategies for businesses to create a market for ecological products and most importantly make friendly products that will be useful to public health and be competitive. In connection with this work there was estimated production company, determined the level of implementation of ecological marketing and a model of development and implementation of an enterprise.